Remarks on Sanskrit and Pali Loanwords in Khmer - Woźnica, Piotr (Investigationes Linguisticae, 2010)
The complicated orthography of Sanskrit and Pali loanwords in Khmer language poses a significant didactical obstacle, as the standard rules of Khmer orthography are irrelevant to those words. After a brief historical introduction, the relations between Sanskrit and Sanskrit > Khmer loanwords’ orthography are explained. Further on, a preliminary classification of Indic loanwords is provided, based on their morphological status and patterns of usage. The most important inference is that a relatively small number of immutable borrowings occurs in most frequently used compounds of Sanskrit and Pali origins. This approach yields two potential solutions to the aforementioned problem. Firstly, a learner of Khmer should study the basics of Sanskrit and Pali orthography and phonology, as they have a tremendous impact on the way borrowings are spelled. Secondly, the learner should note that many Indic loanwords in Khmer are in fact compounds, and observe the distribution patterns of their individual constituents.